Association of fever and infections with the subsequent risk of atopic diseases in children with genetic susceptibility for T1D: Results from the TEDDY cohort study - Palmu, Tiina; Lehtonen, Jussi; Elding Larsson, Helena; Lynch, Kristian F.; Jonsdottir, Berglind; Cilio, Corrado; Schatz, Desmond; Rewers, Marian; Hyöty, Heikki; Lönnrot, Maria (Pediatric allergy and immunology, 2025)
Background The increased prevalence of atopic diseases may be due to lifestyle changes affecting our exposure to microbes. We investigated the association between infections, fever, and atopic diseases in a large international birth cohort setting. Methods 3842 children at genetic risk for type 1 diabetes were followed prospectively for the first 10 years for the occurrence of infections and atopic diseases within The Environmental Determinants of Diabetes in the Young (TEDDY) study. A time‐discrete survival analysis was carried out to evaluate the association of self‐reported febrile and non‐febrile infections (respiratory, gastrointestinal, other, fever alone) and the risk of subsequent atopic eczema, allergic rhinitis, asthma, and allergies. Results The rate of respiratory infections was positively associated with the subsequent risk of asthma (HR 1.30, 95% CI 1.25–1.35, p < .001). Febrile respiratory infections increased the risk of asthma more than non‐febrile ones (febrile respiratory infection HR 1.50, 95% CI 1.42–1.59, p < .001; non‐febrile respiratory infection HR 1.24, 95% CI 1.18–1.30, p < .001). In contrast, fever decreased the positive association of infections with the risk of other atopic diseases. Episodes of fever as the only reported symptom had a negative association particularly with the risk of atopic eczema (HR 0.53, 95% CI 0.39–0.71, p < .001). Conclusions In a longitudinal cohort study, fever shows a clear impact on how infections associate with subsequent atopic diseases. Understanding the modifying role of fever on risk offers new possibilities to explore the mechanisms that mediate the effect of infections in the atopic process.